MINERAL RESOURSE OF UZBEKISTAN AND THEIR GLOBAL IMPORTANCE. COTTON INDUSTRY:HISTORY AND CURRENT ROLE IN THE ECONOMY - Teshaboyeva Nafisa Zubaydulla qizi; Igor Chekulay Vladimirovich; Soibjonova Bahora (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Annotation:this article discusses the mineral resources of Uzbekistan and their significant global importance, as well as the country’s cotton industry and its current role in the national economy. It explains how Uzbekistan has developed its rich mineral base—including gold,  copper, uranium,  and other  valuable  metals—and how these resources contribute to both domestic economic growth and international trade. The article highlights the strategic importance of Uzbekistan’s minerals, which are used in energy production, industry, and technology, making the country an important player in  global  markets.It  also  emphasizes  the  role  of  the  cotton  industry,  which  has historically  been  one  of  Uzbekistan’s  key  agricultural  sectors.  Cotton  production continues to support the rural economy, provide employment, and contribute to export revenues. The article outlines modern reforms and innovations in the cotton sector, including  the  introduction  of  environmentally  friendly  farming  practices, mechanization,  and  digital  technologies  to  increase  productivity  and quality.Furthermore, the article describes efforts to diversify the economy by linking the mineral and cotton industries to broader industrial and manufacturing development. These initiatives have strengthened Uzbekistan’s economic resilience, improved living standards,  and  expanded  its  participation  in  international  trade.Overall,  the  article shows how Uzbekistan’s natural resources and strategic industries—through careful management,  modernization,  and  international  cooperation—play  a  vital  role  in building a strong, competitive, and sustainable economy that successfully balances traditional strengths with modern growth.